A new species of Cardioscarta (Hemiptera: Cicadellidae: Cicadellini) from the Atlantic Forest of southeastern Brazil and key to species of the genus - Pecly, Nathalia H.; Quintas, Victor; Cavichioli, Rodney R.; Mejdalani, Gabriel (Zootaxa, 2018)
The South American genus Cardioscarta Melichar, 1932 includes seven species of colorful sharpshooters. Here we describe and illustrate an additional species, C. aurantia sp. nov., from the Atlantic Forest of southeastern Brazil (state of Rio de Janeiro). The new taxon can be distinguished by the dark brown to black forewing with two large orange areas, one from basal portion of corium to distal portions of discal cells and another covering most of clavus, or with single large orange area on basal two-thirds. A key to species of Cardioscarta is provided and the new species is compared with the other ones of the genus.